Minimally Invasive versus Conventional Aortic Root Surgery: Results of an Intermediate-Volume Center - Elghannam, Mahmoud; Useini, Dritan; Moustafine, Vadim; Bechtel, Matthias; Naraghi, Hamid; Strauch, Justus T.; Haldenwang, Peter Lukas (The Thoracic and Cardiovascular Surgeon, 2023)
Background We evaluate the outcome of aortic root surgery via an upper J-shaped mini-sternotomy (MS) versus full sternotomy (FS) in an intermediate-volume center.Methods Between November 2011 and February 2019, 94 consecutive patients underwent aortic root surgery: 62 (66%) patients were operated via a J-shaped MS (group A) and 32 (34%) patients via FS (group B). The primary endpoints were mortality, major adverse cardiac and cerebral events (MACCE), and reoperation in a 2-year follow-up. The secondary endpoints were perioperative complications and patient's satisfaction with the procedural results.Results Valve sparing root replacement (David procedure) was performed in 13 (21%) of the MS and 7 (22%) of the FS patients. The Bentall procedure in MS versus FS was 49 (79%) versus 25 (78%), respectively. Both groups presented similar mean operation, cardiopulmonary bypass, and cross-clamp times. Postoperative bleeding was 534 ± 300 and 755 ± 402 mL (p = 0.01) in MS and FS, respectively, erythrocyte concentrate substitution was 3 ± 3 and 5.3 ± 4.8 (p = 0.018) in MS and FS, respectively, and pneumonia rates were 0 and 9.4% (p = 0.03) in MS and FS, respectively. The 30-day mortality was 0% in both groups, whereas MACCE was 1.6 and 3% (p = 0.45) in MS and FS, respectively. After 2 years, the mortality and MACCE were 4.6 and 9.5% (p = 0.11) and 4.6 and 0% (p = 0.66) in MS and FS, respectively. The number of patients who were satisfied with the surgical cosmetic results in groups A and B was 53 (85.4%) and 26 (81%), respectively.Conclusion Aortic root surgery via MS is a safe alternative to FS even in an intermediate-volume center. It offers a shorter recovery time and similar midterm results.
Keywords: minimally invasive surgery; includes port access; minithoracotomy; aortic valve and root; aorta/aortic